2018
DOI: 10.5742/mewfm.2018.93192
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of GCKR, MLXIPL and FADS Genes Polymorphisms with Obesity in the Occurrence of Childhood Metabolic Syndrome

Abstract: Objective: Considering the implication of better understanding of metabolic syndrome (MetS) pathophysiology in designing proper preventative and management strategies and the fact that dyslipidemia is one of the early and common features of MetS, the aim of this study was to investigate the interaction of some lipid regulatory genes polymorphisms with obesity in the occurrence of MetS in children. Methods: In this nested case-control study, 300 frozen samples of normal weight and 300 samples of overweight/obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
(31 reference statements)
3
3
2
Order By: Relevance
“…Based on our knowledge, the present study evaluated for the rst time the association of GCKR rs780093 and rs1260326 with MetS risk and its components in an Iranian population; previous studies had focused on rs780094. The minor allele frequency (MAF) of the studied SNPs are different from the studies in the Iranian population [37]. This difference could be due to the sample sizes of these studies were smaller than our study.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Based on our knowledge, the present study evaluated for the rst time the association of GCKR rs780093 and rs1260326 with MetS risk and its components in an Iranian population; previous studies had focused on rs780094. The minor allele frequency (MAF) of the studied SNPs are different from the studies in the Iranian population [37]. This difference could be due to the sample sizes of these studies were smaller than our study.…”
Section: Discussioncontrasting
confidence: 92%
“…In the Iranian population among MetS components, we consistently replicated previous GWAS results that reported signi cant associations of the T-risk allele of selected variants with lower fast blood sugar and higher triglycerides levels [17,18,20,[33][34][35][36]. Only two studies in Iranian children and adolescents (CASPIAN III) have previously demonstrated the association between the rs780094 risk allele and higher triglyceride levels [37,38]. In 74 patients with nonalcoholic fatty liver disease from Tabriz city in the north-west of Iran, the lack of association between the GCKR rs780094 genotypes and lipid pro le was observed.…”
Section: Discussionsupporting
confidence: 87%
“…We consistently replicated previous GWAS results that reported the T allele carriers of selected variants had signi cant associations with lower FBS and higher TG levels among MetS components [17,18,20,[34][35][36][37]. Among Iranian studies, two studies in children and adolescents (CASPIAN III) have previously demonstrated the association between the rs780094 risk allele and higher triglyceride levels [38,39]. The correlation of rs1260326 and rs780094 with these MetS components has also been con rmed in our previous cross-sectional study in adults [27].…”
Section: Discussionsupporting
confidence: 89%
“…Based on our knowledge, the present study evaluated for the rst time the association of GCKR rs780093 with MetS risk and its components in an Iranian population; previous studies had focused on rs780094. The minor allele frequency (MAF) of the selected GCKR SNPs was different from the other Iranian population study [38]. This difference could be Because of the current study's greater sample size.…”
Section: Discussioncontrasting
confidence: 61%
“…We consistently replicated previous GWAS results that reported the T allele carriers of selected variants had significant associations with lower FBS and higher TG levels among MetS components [ 22 , 23 , 25 , 39 42 ]. Among Iranian studies, two studies in children and adolescents (CASPIAN III) have previously demonstrated the association between the rs780094 risk allele and higher triglyceride levels [ 43 , 44 ]. The correlation of rs1260326 and rs780094 with these MetS components has also been confirmed in our previous cross-sectional study in adults [ 32 ].…”
Section: Discussionmentioning
confidence: 99%